[P03] Medium Term Outcomes in Patients Undergoing Atherectomy and Antirestenotic Therapy vs. Bypass for Long Infrainguinal In Stent Occlusions. (November 2022) - Vijaynagar, Badri; Katsogridakis, Emmanuel; Saratzis, Athanasios
Abstract : Objective: The purpose of this study was to report medium term clinical outcomes following atherectomy and antirestenotic therapy (DAART) for in stent occlusions below the inguinal ligament and compare these with femoro-popliteal bypass. Methods: Data were prospectively collected for all consecutive patients who presented with chronic limb threatening ischaemia and had undergone previous arterial stenting (femoro-popliteal segment) between October 2018 and October 2021 in a single tertiary vascular unit. Outcomes, including amputation free survival, patency, and target lesion revascularisation (TLR), were compared between those having DAART vs . bypass. All patients were entered into a uniform surveillance programme, including three monthly duplex scans. Results: Of 26 patients, 14 (four female; 28%) underwent DAART vs. 22 who underwent femoro-popliteal bypass (three female; 14%). Lesions were comparable in terms of length of occlusion (19 cm vs. 21 cm, p = .09) and number of occluded stents (two vs. two, p = .44). Severe calcification of target lesions was common and did not differ between groups (65% vs . 63%, p = .19). Over a median follow up of 18 months (range 4 – 36 months), there were no differences in amputation free survival (71% vs . 68%, p = .10) or primary assisted patency (86% vs . 90%). Patients having DAART were more likely to require TLR (42% vs . 32%, p = .01). Conclusion: This series with prospective uniform follow up including frequent imaging shows that percutaneous DAART for in stent occlusions below the inguinal ligament has promising results, even when compared with bypass. Re-intervention rates, however, are high in both arms, especially those having DAART.